Cortical and thalamic projections to cytoarchitectural areas 6Va and 8C of the marmoset monkey: Connectionally distinct subdivisions of the lateral premotor cortex. Issue 8 (10th March 2015) - Burman, Kathleen J.; Bakola, Sophia; Richardson, Karyn E.; Yu, Hsin‐Hao; Reser, David H.; Rosa, Marcello G.P.
ABSTRACT We studied the afferent connections of two cytoarchitectural subdivisions of the caudolateral frontal cortex, areas 6Va and 8C, in marmoset monkeys. These areas received connections from the same set of thalamic nuclei, including main inputs from the ventral lateral and ventral anterior complexes, but differed in their patterns of corticocortical connections. Areas 8C and 6Va had reciprocal interconnections, and received similar proportions of afferents from premotor areas 6M and 6DC, and from the prefrontal cortex. However, area 8C received stronger inputs from frontal areas that have been implicated in oculomotor functions, whereas area 6Va received stronger projections from the primary motor area. Somatosensory projections to area 6Va were generally stronger than those to area 8C, and originated from several areas; in contrast, only the second somatosensory area (S2) sent major inputs to area 8C. Finally, although both 6Va and 8C received major inputs from the rostral posterior parietal cortex (putative homologs of areas PE, PF, and PFG), area 8C also received a variety of smaller connections from posterior midline, caudal posterior parietal, and extrastriate areas. Statistical analyses revealed that the pattern of connections of area 8C is more akin to that characterizing a premotor area, rather than a prefrontal area. We conclude that cytoarchitectural area 6Va in the marmoset is similar to ventral premotor areas identified in other simian primates, and that area 8C corresponds to a specialized subdivision of the caudal premotor complex where visual information for the guidance of movements is likely to be emphasized. J. Comp. Neurol. 523:1222–1247, 2015. © 2015 Wiley Periodicals, Inc.